Ant body size mediates functional performance and species interactions in carrion decomposer communities. (22nd March 2022) - Nooten, Sabine S.; Chan, Kin H.; Schultheiss, Patrick; Bogar, Taylor A.; Guénard, Benoit
Abstract: Growing concern over rapid species declines and extinctions has led to considerable interest in the role of biodiversity for maintaining ecological processes. However, the loss of particular species has more pronounced effects on ecosystem services than others, highlighting the importance of key functional species traits and their relationships to ecosystem functioning. Human‐induced disturbances, such as species invasions, land use changes, or abiotic changes, appear to disproportionally impact larger species rather than smaller ones. The loss of large‐bodied species in the community diminishes key ecosystem services like seed dispersal, pest control, pollination and decomposition. Here, we use carrion, a nutrient‐rich ephemeral resource, to test the hypotheses that ants positively affect decomposition rates and that their role in the necrophilous community—as predator or decomposer—is mediated by body size. We further investigate the relative contribution of maggots versus ants to biomass decomposition. Our results show that ants contributed positively to the decomposition process. Moreover, decomposition was shaped by an intricate interplay between competition and predation among the guild of decomposer insects. As predicted, larger ants show a double action in increasing decomposition rate and predating on maggots, while small ants are rather inefficient decomposers and did not act as predators on other decomposer species. Our study shows that differentiating key taxonomic groups in function of their body size is key to untangle the diversity and directions of the various roles they play within complex ecological processes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.